Toward Annealing‐Stable Molybdenum‐Oxide‐Based Hole‐Selective Contacts For Silicon Photovoltaics. Issue 4 (19th February 2018) - Essig, Stephanie; Dréon, Julie; Rucavado, Esteban; Mews, Mathias; Koida, Takashi; Boccard, Mathieu; Werner, Jérémie; Geissbühler, Jonas; Löper, Philipp; Morales‐Masis, Monica; Korte, Lars; De Wolf, Stefaan; et al.
Abstract : Molybdenum oxide (MoOX ) combines a high work function with broadband optical transparency. Sandwiched between a hydrogenated intrinsic amorphous silicon passivation layer and a transparent conductive oxide, this material allows a highly efficient hole‐selective front contact stack for crystalline silicon solar cells. However, hole extraction from the Si wafer and transport through this stack degrades upon annealing at 190 °C, which is needed to cure the screen‐printed Ag metallization applied to typical Si solar cells. Here, we show that effusion of hydrogen from the adjacent layers is a likely cause for this degradation, highlighting the need for hydrogen‐lean passivation layers when using such metal‐oxide‐based carrier‐selective contacts. Pre‐MoOX ‐deposition annealing of the passivating a‐Si:H layer is shown to be a straightforward approach to manufacturing MoOX ‐based devices with high fill factors using screen‐printed metallization cured at 190 °C. Abstract : Performance loss due to post‐fabrication annealing of MoOx‐based silicon heterojunction solar cells is investigated. This loss is linked to band‐bending diminution using surface photovoltage measurements, and to hydrogen effusing from the adjacent amorphous silicon layers and interacting with MoOx. Annealing the sample prior to MoOx deposition mitigates this phenomenon, offering a route toward annealing‐stable MoOx‐based silicon solar cells.